New Dacron tissue colonisable keratoprosthesis: clinical experience. Issue 9 (September 1995) - Pintucci, S; Pintucci, F; Cecconi, M; Caiazza, S
Abstract : BACKGROUND--Keratoprostheses (KPs) are made of an optical cylinder integrated with a supporting element which conditions their biocompatibility. A new KP with a Dacron tissue colonisable support has been designed in order to reduce significantly the complication rate. METHODS--This new KP was implanted into 20 eyes of 20 patients with bilateral corneal blindness unsuited to a corneal implant. The follow up ranged from 24 to 96 months. RESULTS--All 20 patients had some improved visual acuity with 13 retaining this improvement for more than 2 years. CONCLUSION--These favourable results may be indicative of the reliability of the new KP.